ANALISIS PENGENDALIAN KUALITAS PRODUK CABLE PADA PT AMBER KARYA - Muhammad Ramadhan; Arista, Anggia (LPPM Universitas Putera Batam, 2025)
PT Amber Karya is a manufacturing that produces cable as sembly wire harness for industry and households. Types of cable wire harness that are produced such as High Definition Multimedia Interface (HDMI) cables, Universal Serial Bus (USB) and Local Area Network (LAN) cables. Based on the data obtained, production using the LAN cable type Extrusion machine has a defect rate exceeding the tolerance limit reaching 6,169 or 8.23%. The purpose of this to calculate the most defects and the factors that cause defects to appear and provide the best proposal to reduce defects so as to improve the quality of the cable. The sigma method is the approach that is employed with five stages, namely the DMAIC phase, Define, measure, Analyse, Improve, and Control. The results showed that after implementing improvements the defect rate became 2,107 or 2.8%. The sigma level improved from 2.9 (82,253) to 3.4 (28,092). So That, the quality of cable can be improved.